2008
DOI: 10.1007/bf03086202
|View full text |Cite
|
Sign up to set email alerts
|

Complications and lead extraction in cardiac pacing and defibrillation

Abstract: The only indications for which lead extraction may be really necessary are infected pacing or defibrillation systems. Superfluous non-functional leads can on the whole be more safely abandoned than extracted. Improvements in lead extraction will be more helped by designing and implanting leads that can be more easily removed than current models, than with better extraction tools. Still, as infection and hence lead extraction usually follows surgical interventions of a pacing or defibrillation system, avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…Regarding the specific placement of the proximal defibrillation coil in dual-coil ICD lead systems, the presence of a proximal SVC defibrillation coil may add additional risk in transvenous lead extraction [1,58,59]. Several publications describe the proximal coil of dual-coil lead systems as a special technical problem, consuming additional time and increasing risk for serious complications [59][60][61]66]. Despite these reports there are no reliable clinical data comparing the extraction of dualversus single-coil leads.…”
Section: Transvenous Icd-lead Extractionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding the specific placement of the proximal defibrillation coil in dual-coil ICD lead systems, the presence of a proximal SVC defibrillation coil may add additional risk in transvenous lead extraction [1,58,59]. Several publications describe the proximal coil of dual-coil lead systems as a special technical problem, consuming additional time and increasing risk for serious complications [59][60][61]66]. Despite these reports there are no reliable clinical data comparing the extraction of dualversus single-coil leads.…”
Section: Transvenous Icd-lead Extractionmentioning
confidence: 98%
“…Even in very experienced hands, transvenous ICD-lead extraction is associated with a significant interventionrelated complication rate [2,[56][57][58][59][60][61][62][63][64][65][66][67]. The extraction of dual-coil ICD leads may be associated with an increased risk, compared to the extraction of single-coil leads or pacing leads [1,58,59].…”
Section: Transvenous Icd-lead Extractionmentioning
confidence: 99%
“…It has been suspected for some time that the extraction of dual‐coil leads may be associated with increased risk compared to single‐coil leads given the fibrous tissue in growth and adherence of the coil to the thin wall of the SVC or right atrium . Epstein et al recently reported a retrospective study involving extraction of 273 single‐coil leads and 1,791 dual‐coil leads from nine high‐volume centers.…”
Section: Disadvantages Of Dual‐coil Leads (Transvenous Extraction)mentioning
confidence: 99%
“…An inherent sequela of this is an increased need for CIED extraction which carries a significant acute morbidity and mortality and is associated with poor long‐term outcomes . The decision to proceed with CIED extraction needs to be weighed carefully, particularly in cases where extraction is not absolutely clinically mandated . Appropriate indications for CIED and lead extraction are detailed in the 2008 Heart Rhythm Society (HRS) Consensus document.…”
Section: Introductionmentioning
confidence: 99%
“…clinically mandated. 2,[4][5][6][7] Appropriate indications for CIED and lead extraction are detailed in the 2008 Heart Rhythm Society (HRS) Consensus document. This document and published registry data serve as a guide to best practice but these repositories make no mention of the risk of repeat transvenous lead extraction (TLE).…”
mentioning
confidence: 99%